Immune-correlates analysis of an HIV-1 vaccine efficacy trial reveals an association of nonspecific interferon-γ secretion with increased HIV-1 infection risk: a cohort-based modeling study. - Yunda Huang; Ann Duerr; Nicole Frahm; Lily Zhang; Zoe Moodie; Steve De Rosa; M Juliana McElrath; Peter B Gilbert (PLoS ONE, 2014)
Elevated risk of HIV-1 infection among recipients of an adenovirus serotype 5 (Ad5)-vectored HIV-1 vaccine was previously reported in the Step HIV-1 vaccine efficacy trial. We assessed pre-infection cellular immune responses measured at 4 weeks after the second vaccination to determine their roles in HIV-1 infection susceptibility among Step study male participants.We examined ex vivo interferon-γ (IFN-γ) secretion from peripheral blood mononuclear cells (PBMC) using an ELISpot assay in 112 HIV-infected and 962 uninfected participants. In addition, we performed flow cytometric assays to examine T-cell activation, and ex vivo IFN-γ and interleukin-2 secretion from CD4(+) and CD8(+) T cells. We accounted for the sub-sampling design in Cox proportional hazards models to estimate hazard ratios (HRs) of HIV-1 infection per 1-log(e) increase of the immune responses.We found that HIV-specific immune responses were not associated with risk of HIV-1 infection. However, each 1-log(e) increase of mock responses measured by the ELISpot assay (i.e., IFN-γ secretion in the absence of antigen-specific stimulation) was associated with a 62% increase of HIV-1 infection risk among vaccine recipients (HR = 1.62, 95% CI: (1.28, 2.04), p<0.001). This association remains after accounting for CD4(+) or CD8(+) T-cell activation. We observed a moderate correlation between ELISpot mock responses and CD4(+) T-cells secreting IFN-γ (ρ = 0.33, p = 0.007). In addition, the effect of the Step vaccine on infection risk appeared to vary with ELISpot mock response levels, especially among participants who had pre-existing anti-Ad5 antibodies (interaction p = 0.04).The proportion of cells, likely CD4(+) T-cells, producing IFN-γ without stimulation by exogenous antigen appears to carry information beyond T-cell activation and baseline characteristics that predict risk of HIV-1 infection. These results motivate additional investigation to understand the potential link between IFN-γ secretion and underlying causes of elevated HIV-1 infection risk among vaccine recipients in the Step study.